Cultura jurídica da liberdade: autos cíveis e petições envolvendo escravos e forros na cidade de São Paulo, Século XVIII - Oliveira, Felipe Garcia De [UNIFESP] (2020)
This Master’s thesis analyses civil cases and petitions involving slaves and freedmen as claimants and defendants in São Paulo city in the eighteenth century and seek to recover the dynamics of institutions and agents. In this regard, it is our focus the legal culture linked to the demands of slaves and freedmen, based on analysis of civil cases and petitions about claims to freedom, illegal slavery, requests for annulment of manumission and recovery of debts. This research also seeks to understand the social incorporation and forms of resistance of their as discuss their social performance. The spatial cutting around the city is grounded in that it was the administrative and commercial headquarters of the region. In the eighteenth century, the capitania of São Paulo underwent deep transformations in demographic growth, characterized, mainly by the intensive entry of contingent of African slaves, especially in the second half of the century, with the expansion of sugarcane plantations in the wake of the economic dynamism present in the paulista society.